Каждому свое - Пикуль Валентин Саввич (Современник, 1990)
Экземпляры: Селтинская районная библиотека (к/х) (20220719) / Инвентарный номер: 152145 / Цена: / Авт.знак: П32 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6